SISTEM INFORMASI PENGELOLAAN DANA BANTUAN OPERASIONAL SEKOLAH (BOS) SMK AL-HASANAIN BERAIM BERBASIS PHP DAN MySQL - Mohammad Taufan Asri Zaen; Baiq Sri Mardiani (LPPM STMIK Lombok, 2018)
School Operational Assistance (BOS) is a government program to provide funds for non-personnel education units, primary and secondary costs as a means of implementing the 9-year compulsory education program. BOS funds are intended to alleviate all forms of education costs for all students. BOS management is currently still using a manual system, and thats no exception at Al Hasanain Beraim Vocational School. This manual management errors and hassle because the BOS revision must go to the Education Office. Information System (SI) the management of BOS funds was built to facilitate schools. This SI contains an activity plan submission and a one-year budget, and a general cash book for BOS funds that is carried out every semester. This system is built using by PHP language and MySQL database the system development life cycle (SDLC) development method. This information system can help the school in the process of planning school fund activities (RKAS) every year and preparation of real funds in the form of general cash books (BKU), makes it an easier for administrators to check operational of school assistance funds that have been budgeted for the country's financial statements that produce data accurate and complete and timely.